Improvements in thermoforming simulation by use of 3D digital image correlation - B. Van Mieghem; F. Desplentere; A. Van Bael; J. Ivens (eXPRESS Polymer Letters, 2015)
Numerical simulation tools for the thermoforming of unfilled thermoplastic polymers already exist for a while, but are seldom used to full extent in industry. When it is used, it is mostly only for comparative studies and prediction of relative wall thickness. One of the major reasons is the difficulty to correctly calibrate and integrate all necessary material and process parameters into the simulation software. This paper introduces and validates a methodology, in which digital image correlation (DIC) is used as the key enabling technology that improves the knowledge of the process parameters and optimizes simulation accuracy by taking away a number of uncertainties and assumptions. DIC in combination with infrared thermal measurements and pressure monitoring is used to track sheet sagging and bubble inflation of a HIPS sheet, the two main process steps in the thermoforming of positive (male) products or the only two steps in the case of free forming. The results of these in-situ measurements are used as a guideline for selecting the correct input parameters in the commercial thermoforming simulation software T-SIM®. A similar methodology can be further implemented for subsequent process steps such as forming and cooling or even to validate the material data used in the simulation software.